UJI EFEK HEPATOPROTEKTIF INFUS HERBA PEGAGAN (Centella asiatica, (L.) Urb) PADA TIKUS PUTIH GALUR WISTAR YANG TERINDUKSI PARASETAMOL - Islamiyah Neda Rahayu; Farida Hayati (Universitas Islam Indonesia, 2005)
ABSTRACTAcetaminophen is a kind of analgetic-antipyretic drug which the usage in excessive dose willcause the liver damage. Pegagan herb (Centella asiatica, L) is one of plant which is used to protectthe liver from various damage of drug. A research to study the hepatoprotective effect of pegaganherb infusion on acetaminophen induced wistar rat has been conducted. This research was aimedto find how excellent pegagan herb protects the liver from the damages caused by acetaminophenand find the data of hepatoprotective of pegagan herb’s dose effect span in infussion form throughthe SGPT enzym and hyspatology of liver cell analysis. This research used the completed randomof unidirectoral pattern method, using wistar strain white rat as the tested animals, weight 200 g 10%, age 5-8 weeks. The way of attemp: 36 rat were divided into 6 groups were each groups had 6rat. For the treatment, Group I was controlled by aquadest. Group II was given acetaminophensuspention dose 2,5 g/kg BB. Group III-IV was given pegagan herb infussion 0,027; 0,054; 0,0108;0,216 g/kg BB once in a day for a week and 8 hours after that, on the seventh day was givenacetaminophen suspention dose 2,5 g/kg BB. Blood taking was conducted by orbitalis sinus beforeth treatment, 8 hours after the seventh day treatment and 24 hours after acetaminophen was given.SGPT data was analysed by ANOVA statistical test, where if found the significant difference, itwould continue by Tuckey Test with 95% as significant standar. Then continued by hyspatology teston liver cell of rat. The result of this research showed that pegagan herb infussion dose 0,027;0,054; 0,108; 0,216 g/kg BB had a hepatoprotective effect on acetaminophen inducted white ratsuccessively 34,19%; 62,52%; 78,62%; 85,69%. And the result of qualitative analysis by histologyanalysis showed that pegagan herb had hepatoprotective effect.Keyword: Hepatoprotective, Pegagan Herb,Acetaminophen